PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM DESA WISATA DI DESA KALONGAN KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Yehezkiel Lucky Ririhena Lucky Ririhena; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Community empowerment through the Tourism Village Program is a strategic approach to community-based tourism development aimed at improving social welfare and local independence. Kalongan Village, located in Ungaran Timur District, Semarang Regency, possesses diverse natural and cultural tourism potentials. However, the implementation of the Tourism Village Program still faces various challenges in empowering the local community. This study aims to analyze the process of community empowerment through the Tourism Village Program in Kalongan Village and to examine the factors related to its implementation. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The informants consist of representatives from the Semarang Regency Tourism Office, Kalongan Village Government, Tourism Awareness Group (Pokdarwis), and local community members. The results indicate that community empowerment in Kalongan Village has been carried out through the stages of awareness-building, capacity building, and empowerment. Nevertheless, the empowerment process has not yet been fully optimized due to limitations in human resource capacity, uneven community participation, and weak coordination among stakeholders. The study concludes that the Tourism Village Program in Kalongan Village has significant potential to enhance community welfare, but it requires strengthened capacity building, continuous assistance, and more inclusive empowerment strategies. Therefore, it is recommended that local stakeholders intensify community development efforts, strengthen local institutions, and optimize community participation in tourism village management.